Presentation is loading. Please wait.

Presentation is loading. Please wait.

Algebra Recap Solve the following equations (i) 3x + 7 = 32 - 2x (ii) 3x + 1 = 5x – 13 (iii) 3(5x – 2) = 4(3x + 6) (iv) 3(2x + 1) = 2x + 11 (v) 2(x + 2)

Similar presentations


Presentation on theme: "Algebra Recap Solve the following equations (i) 3x + 7 = 32 - 2x (ii) 3x + 1 = 5x – 13 (iii) 3(5x – 2) = 4(3x + 6) (iv) 3(2x + 1) = 2x + 11 (v) 2(x + 2)"— Presentation transcript:

1 Algebra Recap Solve the following equations (i) 3x + 7 = x (ii) 3x + 1 = 5x – 13 (iii) 3(5x – 2) = 4(3x + 6) (iv) 3(2x + 1) = 2x + 11 (v) 2(x + 2) – 3(x – 3) = x + 7 3x + 2x = 32 – 7 5x = 25 x = 25/5 x = 5 3x – 5x = -13 – 1 -2x = -14 2x = 14 x = 7 15x – 6 = 12x x – 12x = x = 30 x = 10 6x + 3 = 2x x – 2x = 11 – 3 4x = 8 x = 2 2x x + 9 = x + 7 2x – 3x – x = 7 – 4 – 9 -2x = -6 x = 3

2 Algebraic Fractions 4x + 12 = 8 5x +14 = 11 7x – 5 = x x – 5 = 5 2x – = 3x (4x + 12) = 2(8) 2 4x + 12 = 16 4x = 4 x = 1 4(5x + 14) = 4(11) 4 5x + 14 = 44 5x = x = 30 x = 6 8(7x - 5) = 8(9) 8 7x - 5 = 72 7x = 77 x = 11 12(5x - 4) - 12(3x – 5) = 12(5) 4 3 3(5x - 4) - 4(3x – 5) = 60 15x x + 20 = 60 3x + 8 = 60 3x = 52 x = 17⅓ 20(2x - 3) + 20(1) = 20(3x - 2) (2x – 3) + 10(1) = 4(3x – 2) 10x – = 12x – 8 10x -5 = 12x – 8 10x – 12x = x = -3 x = ⅔

3 Quadratics x² + 10x + 9 x² - 15x + 26 x² - 8x – 33 2x² + 15x + 7 3x² + 8x + 4 2x² - 7x - 15


Download ppt "Algebra Recap Solve the following equations (i) 3x + 7 = 32 - 2x (ii) 3x + 1 = 5x – 13 (iii) 3(5x – 2) = 4(3x + 6) (iv) 3(2x + 1) = 2x + 11 (v) 2(x + 2)"

Similar presentations


Ads by Google